Bimbingan Konseling Islam Berbasis Ilmu Dakwah - Arifin, Isep Zainal (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2008)
Bimbingan dan Konseling/Penyuluhan Islam (Islamic Guidance and Counseling) has been grown up in Dakwah Faculty rather than Tarbiyah. In fact, this disciplines more close to education field. This phenomenon caused the needs of Dakwahâs science basic to develop it. The methodology which uses are; Al-ThurÃ»q al-IstinbÃ¢th, Al-ThurÃ»q al-IqtibÃ¢s, Al-ThurÃ»q al-Istiqra,âAl-Jamâu Bayna ÃâqÃ»l al-Shafiyyah wa NufÃ»s al-Zakiyyah. In other or conventional counseling, BKI/BPI field become one of the methodology of counselling for all with psychology counseling as the the root, not pedagogic counseling.